A nitrogen-doped graphitized carbon bifunctional catalyst, a preparation method and application thereof

By preparing nitrogen-doped graphitized carbon catalysts, the problems of catalyst metal loss and single function were solved, and efficient thermocatalysis and electrocatalysis of HMF were achieved, which are suitable for the conversion of biomass-based platform compounds.

CN118491552BActive Publication Date: 2026-11-03NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410425866.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2026-11-03
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

Existing catalysts suffer from metal loss during the oxidation of HMF to FDCA and cannot simultaneously achieve efficient thermocatalysis and electrocatalysis.

Method used

Nitrogen-doped graphitized carbon catalysts were prepared via a complexation-carbonization-acid etching method. Transition metal salts were complexed with nitrogen-containing organic carboxylic acids in deionized water, followed by calcination under an inert atmosphere and treatment with acid solution to form highly active and stable carbon-based catalysts.

Benefits of technology

It achieves complete conversion of HMF and high FDCA yield, avoids metal loss, has good catalyst stability, and is simple to prepare, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118491552B_ABST
    Figure CN118491552B_ABST
Patent Text Reader

Abstract

The application discloses a nitrogen-doped graphitized carbon bifunctional catalyst and a preparation method and application thereof, and the preparation method comprises the following steps: dissolving a transition metal salt and a nitrogen-containing organic carboxylic acid in deionized water, wherein the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid or a derivative thereof, adding dicyandiamide or melamine in the solution, and obtaining a uniform mixed precipitate through heating and stirring; calcining the precipitate under an inert atmosphere; subsequently, heating the product in an acid solution, centrifugally separating and washing the product until the supernatant is neutral; and drying the product to obtain the nitrogen-doped graphitized carbon catalyst. The transition metal is complexed with the nitrogen-containing organic matter, and then the graphitized carbon catalyst is formed through calcination and acid washing, the preparation method is beneficial to uniformly dispersing nitrogen atoms and reducing the temperature for forming the graphitized carbon. Through the three steps of dissolution and complexation, high-temperature calcination and acid washing and etching, the carbon-based bifunctional catalyst with high catalytic activity and good stability can be obtained, and the carbon-based bifunctional catalyst can be used for thermocatalysis and electrocatalysis to oxidize furan alcohol and aldehyde into corresponding furan acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and in particular to a nitrogen-doped graphitized carbon bifunctional catalyst, its preparation method, and its application. Background Technology

[0002] Biomass, as a novel, clean, and renewable non-fossil resource, is considered a potential fossil fuel alternative for mitigating climate risks and meeting the requirements of environmental protection and sustainable development. 5-Hydroxymethylfurfural (HMF), a biomass-derived platform molecule, is considered a multifunctional precursor to a range of valuable chemical substances. For example, 2,5-furandicarboxylic acid (FDCA) can be directly synthesized via HMF oxidation. The biomass-based platform compound FDCA, with its significant value, can not only be used as a monomer in the production of bioplastics such as polyesters, polyamides, and polyurethanes, but also as a substitute for petroleum-based PTA in polymer production.

[0003] In recent years, a large number of catalysts for the oxidation of HMF to FDCA have been studied, including noble metal catalysts and non-noble metal catalysts. Some noble metal catalysts have shown excellent catalytic oxidation performance of HMF, such as Pt / (C-Pb), Au / HY, and Pt-CeO2 / C, which can achieve highly selective conversion of HMF under relatively mild conditions. However, the rarity and high cost of noble metals greatly limit their industrial-scale application. In electrocatalysis, although noble metal catalysts have a lower reaction onset potential, their electrolytic current density is also lower; while non-noble metal materials are inexpensive and abundant. Current research shows that under the drive of an applied potential, Ni-based catalysts, Co-based catalysts, and their alloy catalysts exhibit far superior performance to noble metal catalysts in the electrocatalytic oxidation of HMF.

[0004] Even so, in the thermal and electrocatalytic oxidation of HMF, metal catalysts inevitably suffer metal loss as the reaction proceeds. Theoretically, carbon catalysts can avoid this metal loss problem, but currently, carbon catalysts exhibit very poor activity in the thermal oxidation of HMF. Furthermore, existing transition metal and non-metal catalysts only possess one function—thermal or electrocatalytic—in the oxidation of HMF to FDCA, making it impossible for a single catalyst to simultaneously meet the requirements of efficient thermal and electrocatalysis. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to develop a bifunctional carbon-based catalyst that can be used for both thermocatalytic and electrocatalytic oxidation of HMF to FDCA.

[0006] To address the aforementioned technical problems, the first aspect of this invention provides a method for preparing a nitrogen-doped graphitized carbon bifunctional catalyst, comprising the following steps:

[0007] S1. Dissolve a transition metal salt and a nitrogen-containing organic carboxylic acid in deionized water, wherein the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid or its derivative, add dicyandiamide or melamine to the solution, and heat and stir to obtain a uniformly mixed precipitate.

[0008] S2. The precipitate obtained in step S1 is calcined under an inert atmosphere at a temperature of 400–1500°C for 1–7 hours.

[0009] S3. Heat the product obtained in step S2 in an acidic solution, centrifuge and wash until the supernatant is neutral.

[0010] S4. Dry the product obtained in step S3 to obtain the nitrogen-doped graphitized carbon bifunctional catalyst.

[0011] This invention uses nitrogen-doped graphitized carbon as a support. Doping can enhance the catalytic activity of the carbon catalyst, and transition metal catalysis can improve the degree of graphitization, thereby improving the anodic corrosion resistance of the carbon catalyst. By using chemical dissolution, calcination, and hot acid washing, a bifunctional nitrogen-doped carbon-based catalyst with high catalytic activity and good stability can be obtained, which can be used for both thermocatalysis and electrocatalysis of HMF oxidation to FDCA.

[0012] Further, in step S1, the molar ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 10:1 to 0.1:1, and the molar ratio of the transition metal salt to dicyandiamide or melamine is 10:1 to 0.1:1.

[0013] Furthermore, in step S1, the ratio of the total mass of the transition metal salt and the nitrogen-containing organic carboxylic acid to the mass of deionized water is 1:10 to 1:2000.

[0014] Furthermore, the nitrogen-containing organic carboxylic acid is selected from one or more of ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid monosodium salt, ethylenediaminetetraacetic acid disodium salt, ethylenediaminetetraacetic acid trisodium salt, ethylenediaminetetraacetic acid tetrasodium salt, ethylenediaminetetraacetic acid monopotassium salt, ethylenediaminetetraacetic acid dipotassium salt, ethylenediaminetetraacetic acid tripotassium salt, and ethylenediaminetetraacetic acid tetrapotassium salt.

[0015] Furthermore, in step S1, the heating temperature is 30–130°C, and the stirring time is 1–7 hours.

[0016] Furthermore, in step S3, the acid solution is selected from at least one of sulfuric acid, hydrochloric acid, and nitric acid, the mass fraction of the acid solution is 1% to 30%, and the treatment time is 1 to 7 hours.

[0017] The principles of each step in this invention are as follows: Nitrogen-containing organic carboxylic acids are used as chelating agents to form complexes with transition metal salts in deionized water. The addition of dicyandiamide or melamine can improve the uniformity of nitrogen-doped active sites, effectively improving the conductivity of the support material and giving it better electron transport performance and conductivity. During calcination, the transition metal catalyzes the formation of graphitized carbon materials from organic matter. Both doping and graphitization can promote electron transfer in carbon materials and improve their catalytic performance. Acid solution heat treatment can oxidize and remove disordered carbon, thereby further improving the degree of graphitization and etching away the transition metal embedded in the carbon layer. This avoids the problem of reduced purity of FDCA products due to catalyst metal loss in later catalytic applications and reduces the difficulty of FDCA purification and impurity removal.

[0018] A second aspect of this invention provides a nitrogen-doped graphitized carbon bifunctional catalyst, prepared using the method described above. This catalyst is a carbon-based catalyst, which has a significant cost advantage over noble metal catalysts, is environmentally friendly, and exhibits good catalytic performance. When applied to thermocatalytic and electrocatalytic HMF oxidation reactions, it can achieve complete HMF conversion under mild conditions.

[0019] The third aspect of this invention provides an application of a nitrogen-doped graphitized carbon bifunctional catalyst, wherein the nitrogen-doped graphitized carbon bifunctional catalyst is used for the thermocatalytic oxidation of 5-hydroxymethylfurfural, and the reaction conditions are: temperature 50-95℃, oxygen pressure 0.1-0.5MPa, reaction time 10-16h, and reactant concentration 1-50mM.

[0020] The present invention also provides another application of nitrogen-doped graphitized carbon bifunctional catalyst, wherein the nitrogen-doped graphitized carbon bifunctional catalyst is prepared into an electrode as the anode of an electrolysis system for electrocatalytic oxidation of 5-hydroxymethylfurfural, and the reaction conditions are: current density 5-20mA and reactant concentration 1-50mM.

[0021] Furthermore, the preparation method of the anode in the electrolysis system is as follows: Take 5-50 mg of nitrogen-doped graphitized carbon bifunctional catalyst, mix it ultrasonically with naphthol, water, and ethanol, coat the resulting coating solution onto the current collector, and dry it to obtain the desired electrode. The electrocatalytic reaction conditions are mild, requiring no high temperature, high pressure, or oxygen. In alkaline solution, it can efficiently electrocatalyze the oxidation of HMF.

[0022] The nitrogen-doped graphitized carbon bifunctional catalyst of the present invention exhibits excellent thermocatalytic and electrocatalytic performance in HMF oxidation, and can achieve complete conversion of HMF. At the same time, the catalytic oxidation product FDCA has a high yield and the catalyst has high stability.

[0023] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) This invention proposes a carbon-based catalyst that can simultaneously achieve thermocatalysis and electrocatalysis of 5-hydroxymethylfurfural oxidation, providing a new direction for biomass catalytic oxidation technology.

[0025] (2) The nitrogen-doped graphitized carbon bifunctional catalyst of the present invention can avoid the problem of metal loss. By improving the degree of graphitization through transition metal catalysis, the anodic corrosion resistance of the catalyst can be greatly improved, so that the catalyst has good catalytic activity and stability.

[0026] (3) The present invention uses a complexation-carbonization-acid etching method to prepare a bifunctional catalyst. The preparation method is simple, the conditions are mild, and it is conducive to industrial production.

[0027] (4) The bifunctional catalyst of the present invention has mild reaction conditions, high conversion and yield in the application of thermocatalytic or electrocatalytic oxidation of 5-hydroxymethylfurfural, and has good application prospects. Attached Figure Description

[0028] Figure 1 This is a TEM image of the bifunctional catalyst prepared in Example 1 of this invention.

[0029] Figure 2 This is the elemental spectrum of the bifunctional catalyst prepared in Example 1 of this invention.

[0030] Figure 3 This is a graph showing the performance test results of the bifunctional catalyst prepared in Example 2 of this invention for the thermocatalytic oxidation of HMF.

[0031] Figure 4 This is the LSV curve of the bifunctional catalyst prepared in Example 2 of the present invention as an electrode in the electrolyte.

[0032] Figure 5 This is a graph showing the performance test results of the bifunctional catalyst prepared in Example 2 of this invention for the electrocatalytic oxidation of HMF. Detailed Implementation

[0033] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0034] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0035] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This application specification and embodiments are merely exemplary.

[0036] The present invention provides a nitrogen-doped graphitized carbon bifunctional catalyst with high catalytic activity and good stability, and has dual functions of thermal catalysis and electrocatalytic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid.

[0037] The nitrogen-doped graphitized carbon bifunctional catalyst was prepared by a complexation-carbonization-acid etching method, and the specific preparation process includes the following steps:

[0038] S1. Dissolve the transition metal salt and nitrogen-containing organic carboxylic acid in deionized water. Add dicyandiamide or melamine to the solution, heat and stir to obtain a homogeneous precipitate. The heating temperature is 30–130℃, and the stirring time is 1–7 h. The transition metal salt is any one of nitrate, sulfate, chloride, or acetate; the transition metal is any one of iron, cobalt, chromium, copper, or zinc; the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid (EDTA) or its derivatives, such as EDTA monosodium salt, EDTA disodium salt, EDTA trisodium salt, EDTA tetrasodium salt, EDTA monopotassium salt, EDTA dipotassium salt, EDTA tripotassium salt, or EDTA tetrapotassium salt. This step uses the nitrogen-containing organic carboxylic acid as a chelating agent to complex with the transition metal salt in deionized water. The addition of dicyandiamide or melamine further improves the density and dispersion uniformity of nitrogen-doped active sites, effectively improving the conductivity of the carrier material. In a specific embodiment, the molar ratio of transition metal salt to nitrogen-containing organic carboxylic acid is 10:1 to 0.1:1, the molar ratio of transition metal salt to dicyandiamide or melamine is 10:1 to 0.1:1, and the ratio of the total mass of transition metal salt and nitrogen-containing organic carboxylic acid to the mass of deionized water is 1:10 to 1:2000.

[0039] S2. The precipitate obtained in step S1 is calcined under an inert atmosphere. This step uses calcination to graphitize the carbon matrix, promoting electron transfer and improving catalytic performance. In a specific embodiment, the calcination temperature is 700–1500℃, and the time is 1–7 h. The calcination temperature directly affects the degree of graphitization of the carbon matrix, and the catalytic performance also increases with increasing calcination temperature. When the calcination temperature reaches 700℃, complete conversion of HMF can be achieved, and the yield of the catalytically oxidized product FDCA reaches over 60%. However, when the calcination temperature exceeds 900℃, the catalytic performance decreases slightly.

[0040] S3. The product obtained in step S2 is heated in an acid solution, the acid solution being selected from at least one of sulfuric acid, hydrochloric acid, and nitric acid, with a mass fraction of 1%–30%, for 1–7 hours. After centrifugation and washing, the supernatant is kept neutral. This step oxidizes and removes disordered carbon, further increasing the degree of graphitization, while simultaneously etching away transition metal particles. This prevents residual transition metals in the FDCA product due to metal loss during subsequent catalytic oxidation of HMF, thus improving product purity.

[0041] S4. Dry the product obtained in step S3 at a temperature of 60–120°C for 6–24 hours to obtain a nitrogen-doped graphitized carbon bifunctional catalyst.

[0042] This invention utilizes a transition metal complexed with a nitrogen-containing organic compound, followed by calcination and acid etching to form a graphitized carbon catalyst. This preparation method facilitates the uniform dispersion of nitrogen atoms and reduces the temperature required for graphitized carbon formation. Through three steps—dissolution and complexation, high-temperature calcination, and acid etching—a bifunctional carbon-based catalyst with high catalytic activity and good stability is obtained, which can be used for both thermal and electrocatalytic oxidation of furan alcohols and aldehydes to the corresponding furan acids.

[0043] The nitrogen-doped graphitized carbon bifunctional catalyst prepared by this invention exhibits excellent thermocatalytic and electrocatalytic performance in HMF oxidation. When used as a thermocatalytic HMF catalyst, it requires mild reaction conditions and can achieve high conversion and high FDCA yield under the following reaction conditions: temperature 50-95℃, oxygen pressure 0.1-0.5MPa, reaction time 10-16h, and reactant concentration 1-50mM.

[0044] In electrocatalysis applications, the catalyst is prepared as an electrode to serve as the anode in the electrolysis system. The preparation method is as follows: 5–50 mg of nitrogen-doped graphitized carbon bifunctional catalyst is ultrasonically mixed with naphthol, water, and ethanol. The volume ratio of water to naphthol is 10:1–0.1:1, and the volume ratio of ethanol to water is 10:1–0.1:1. The resulting coating solution is then coated onto a current collector and dried to obtain the desired electrode. Typical reaction conditions are: current 5–20 mA, reactant concentration 1–50 mM. Compared to thermal catalysis, electrocatalysis has kinetic advantages and higher energy utilization efficiency.

[0045] The technical effects of the present invention will be described below with reference to specific embodiments. Unless otherwise specified, the raw materials used in the embodiments of this application were all purchased through commercial channels.

[0046] Example 1

[0047] (1) Take 2.9g of cobalt nitrate and 5g of ethylenediaminetetraacetic acid, add 100ml of water, heat and stir at 100℃, and after mixing evenly, add 5g of dicyandiamide and continue heating and stirring until a pinkish-purple precipitate is obtained.

[0048] (2) The precipitate was placed in a tube furnace with a nitrogen atmosphere at a flow rate of 40 ml / min and heated to 900°C at a heating rate of 5°C / min. After holding at this temperature for 5 h, the temperature was lowered to room temperature to obtain the Co@NC intermediate.

[0049] (3) The Co@NC intermediate was placed in 0.5M sulfuric acid and treated at 80℃ for 5h. After centrifugation and washing, the supernatant was neutral. After washing with deionized water, it was placed in an 80℃ oven and dried for 12h to obtain nitrogen-doped graphitized carbon bifunctional catalyst N-GC-900.

[0050] The morphological characteristics of the nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 1 are shown in the transmission electron microscope image below. Figure 1 As shown, the elemental spectrum is as follows Figure 2 As shown, Figure 1 The catalyst surface showed no metal particles, and the elemental spectrum showed that N was successfully doped onto the carbon support. The presence of Co metal was difficult to observe, indicating that it was thoroughly removed by acid washing.

[0051] The thermocatalytic performance of the nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 1 was tested. 30 ml of 50 mM HMF was placed in a reaction vessel, and 4 equivalents of Na2CO3 and 0.75 g of N-GC-900 were added. The HMF oxidation reaction was carried out at 65 °C and 0.2 MPa O2. After 12 h, the HMF conversion rate was 100% and the FDCA yield was 94%.

[0052] Under the same conditions, the nitrogen-doped graphitized carbon bifunctional catalyst was cycled five times, and its stability was determined. After five cycles, the FDCA yield still reached 80%, indicating that the catalyst has good stability.

[0053] The nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 1 was used to prepare an electrode. The preparation method is as follows: A piece of carbon cloth measuring 0.5 cm × 3.0 cm was cut and ultrasonically treated with anhydrous ethanol and water for 20 min each, then dried for later use. 20 mg of N-GC-900 catalyst was taken, and a coating solution of 500 μL was prepared using a water:ethanol:naphthol ratio of 2:2:1. The coating solution was then coated onto the carbon cloth and dried overnight to obtain the electrode.

[0054] Using an electrochemical workstation, a three-electrode system was constructed, with the prepared electrode as the working electrode, a carbon rod as the counter electrode, an Hg / HgO electrode as the reference electrode, and a 1M KOH alkaline solution as the electrolyte. Using this three-electrode system, 50mM HMF was dissolved in the electrolyte, and an electrochemical catalytic oxidation reaction was performed under an applied current. Under a constant current of 10mA, the reaction achieved 100% HMF conversion and 73% FDCA yield.

[0055] Calculations showed that the energy consumption for preparing FDCA from HMF using a thermocatalytic system was 5040.0 J, while the energy consumption using an electrocatalytic method was significantly reduced to 963.6 J. After normalizing the reaction rate and energy consumption of FDCA, the energy efficiency of preparing FDCA using the electrocatalytic method was approximately 5.9 × 10⁻⁶. -4 mmol g -1 h -1 J -1 This is significantly higher than the 2.3 × 10⁻⁶ of the thermocatalytic method. -5 mmol g -1 h -1 J -1 It is 25.6 times that of thermal catalysis, therefore electrocatalysis has a significant energy advantage over thermal catalysis.

[0056] Example 2

[0057] In this embodiment, the nitrogen-doped graphitized carbon bifunctional catalyst was prepared using the same steps as in Example 1.

[0058] The catalytic performance of the nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 2 was tested. 30 ml of 50 mM HMF was placed in a reaction vessel, and 1 M KOH and 0.75 g N-GC-900 were added. The HMF oxidation reaction was carried out at 65 °C and 0.2 MPa O2. Figure 3 The graph shows the relationship between product concentration and reaction time in the thermocatalytic oxidation of HMF. After 16 h, the conversion rate of HMF was 100%, and the yield of FDCA was 82%.

[0059] Using an electrochemical workstation, a three-electrode system was constructed, with the prepared electrode as the working electrode, a carbon rod as the counter electrode, an Hg / HgO electrode as the reference electrode, and a 1M KOH alkaline solution as the electrolyte. Linear voltammetry (LSV) was then performed using this system. Figure 4 The LSV curves are for 1M KOH solution / 1M KOH+10mM HMF mixed solution / 1M KOH+100mM HMF mixed solution.

[0060] A three-electrode system was used, in which 50 mM HMF was dissolved in the electrolyte, and an electrochemical catalytic oxidation reaction was carried out under an applied current. Figure 5 The figure shows the performance of the bifunctional catalyst in the electrocatalytic oxidation of HMF. The results show that the reaction can achieve 100% HMF conversion and 40% FDCA yield under constant voltage electrolysis of 1.4V vs. RHE.

[0061] Example 3

[0062] In this embodiment, nitrogen-doped graphitized carbon bifunctional catalyst N-GC-700 is prepared. The difference from Example 1 is that the calcination temperature in step (2) is 700℃, while the other steps and process parameters are the same.

[0063] The catalytic performance of the nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 2 was tested. 30 ml of 20 mM HMF was placed in a reaction vessel, and 4 equivalents of Na2CO3 and 0.75 g of N-GC-700 were added. The HMF oxidation reaction was carried out at 65 °C and 0.1 MPa O2. After 12 h, the HMF conversion rate was 100% and the FDCA yield was 91%.

[0064] Example 4

[0065] This embodiment prepares nitrogen-doped graphitized carbon bifunctional catalyst N-GC-800. The difference from Example 1 is that the calcination temperature in step (2) is 800℃, while the other steps and process parameters are the same.

[0066] The catalytic performance of the nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 3 was tested. 30 ml of 20 mM HMF was placed in a reaction vessel, and 4 equivalents of Na2CO3 and 0.75 g of N-GC-800 were added. The HMF oxidation reaction was carried out at 65 °C and 0.2 MPa O2. After 12 h, the HMF conversion rate was 100% and the FDCA yield was 95%.

[0067] Example 5

[0068] This embodiment prepares nitrogen-doped graphitized carbon bifunctional catalyst N-GC-1000. The difference from Example 1 is that the calcination temperature in step (2) is 1000℃, while the other steps and process parameters are the same.

[0069] The catalytic performance of the nitrogen-doped graphitized carbon bifunctional catalyst prepared in Example 4 was tested. 30 ml of 10 mM HMF was placed in a reaction vessel, and 4 equivalents of Na2CO3 and 0.75 g of N-GC-1000 were added. The HMF oxidation reaction was carried out at 60 °C and 0.1 MPa O2. After 12 h, the HMF conversion rate was 100% and the FDCA yield was 83%.

[0070] Comparative Example 1

[0071] The nitrogen-doped graphitized carbon bifunctional catalyst N-GC-600 prepared in this comparative example differs from that in Example 1 in that the calcination temperature in step (2) is 600℃, while the other steps and process parameters are the same.

[0072] The catalysts prepared in Examples 1-5 and Comparative Example 1 were evaluated under the same conditions: reactant concentration of 10 mM HMF, reaction temperature of 50 °C, reaction time of 12 h, and oxygen pressure of 0.5 MPa. The performance evaluation results are shown in Table 1 below.

[0073] Table 1. Catalyst Performance Evaluation Table for Examples and Comparative Examples

[0074] sample Calcination temperature (°C) HMF conversion rate FDCA yield Comparative Example 1 600 100% 7.7% Example 3 700 100% 64.9% Example 4 800 100% 70.5% Example 1 900 100% 71.3% Example 5 1000 100% 66.1%

[0075] Comparative Example 2

[0076] The catalyst Co@NC-900 prepared in this comparative example differs from that in Example 1 in that acid heat treatment is not performed in step (3), and the intermediate is directly dried. Other steps and process parameters are the same.

[0077] ICP testing revealed that the Co content in the catalyst of Comparative Example 2 was 28.2%, while the Co content in the catalyst Co / N-GC-900 of Example 1 was only 0.71%. Under conditions of 10 mM HMF reactant concentration, reaction temperature of 50°C, and oxygen pressure of 0.5 MPa, the HMF conversion rate was 100% and the FDCA yield was 87% after 12 hours. This indicates that the catalyst performance slightly decreased after acid heat treatment, while the atom utilization rate significantly improved.

[0078] Comparative Example 3

[0079] The catalyst Co@NC-1000 prepared in this comparative example differs from that in Example 5 in that acid heat treatment is not performed in step (3), and the intermediate is directly dried. Other steps and process parameters are the same.

[0080] The HMF oxidation reaction was carried out under the conditions of reactant concentration of 10 mM HMF, reaction temperature of 50℃, and oxygen pressure of 0.5 MPa. After 12 h, the HMF conversion rate was 100% and the FDCA yield was 64%. It can be seen that the catalyst calcined at 1000℃ has improved atom utilization and catalytic performance after acid heat treatment.

[0081] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of this disclosure, and all such changes and modifications will fall within the scope of protection of this invention.

Claims

1. An application of a nitrogen-doped graphitized carbon bifunctional catalyst, characterized in that, The nitrogen-doped graphitized carbon bifunctional catalyst was prepared by the following method: S1. Dissolve a transition metal salt and a nitrogen-containing organic carboxylic acid in deionized water. The nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid or its derivative. The nitrogen-containing organic carboxylic acid is used as a chelating agent to complex with the transition metal salt in deionized water. Then, dicyandiamide or melamine is added to the solution, and the mixture is heated and stirred to obtain a uniformly mixed precipitate. The transition metal is a metal salt of Co. S2. The precipitate obtained in step S1 is calcined under an inert atmosphere at a temperature of 400–1500°C for 1–7 hours to form graphitized carbon materials by transition metal catalysis of organic matter. S3. The product obtained in step S2 is heated in an acid solution, centrifuged and washed until the supernatant is neutral, in order to remove disordered carbon by oxidation and simultaneously etch away transition metal particles. S4. Dry the product obtained in step S3 to obtain the nitrogen-doped graphitized carbon bifunctional catalyst. The nitrogen-doped graphitized carbon bifunctional catalyst was used for the thermocatalytic oxidation of 5-hydroxymethylfurfural under the following conditions: temperature 50–95 °C, oxygen pressure 0.1–0.5 MPa, reaction time 10–16 h, and reactant concentration 1–50 mM. Alternatively, the nitrogen-doped graphitized carbon bifunctional catalyst can be prepared as an electrode and used as the anode of the electrolysis system for the electrocatalytic oxidation of 5-hydroxymethylfurfural under the following conditions: current density 5-20 mA and reactant concentration 1-50 mM.

2. The application according to claim 1, characterized in that, In step S1, the molar ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 10:1 to 0.1:1, and the molar ratio of the transition metal salt to dicyandiamide or melamine is 10:1 to 0.1:

1.

3. The application according to claim 2, characterized in that, In step S1, the ratio of the total mass of transition metal salts and nitrogen-containing organic carboxylic acids to the mass of deionized water is 1:10 to 1:2000.

4. The application according to any one of claims 1-3, characterized in that, The nitrogen-containing organic carboxylic acid is selected from one or more of ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid monosodium salt, ethylenediaminetetraacetic acid disodium salt, ethylenediaminetetraacetic acid trisodium salt, ethylenediaminetetraacetic acid tetrasodium salt, ethylenediaminetetraacetic acid monopotassium salt, ethylenediaminetetraacetic acid dipotassium salt, ethylenediaminetetraacetic acid tripotassium salt, and ethylenediaminetetraacetic acid tetrapotassium salt.

5. The application according to claim 1, characterized in that, In step S1, the heating temperature is 30–130°C and the stirring time is 1–7 hours.

6. The application of the nitrogen-doped graphitized carbon bifunctional catalyst according to claim 1, characterized in that, In step S3, the acid solution is selected from at least one of sulfuric acid, hydrochloric acid, and nitric acid, the mass fraction of the acid solution is 1% to 30%, and the treatment time is 1 to 7 hours.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped porous-structure carbon material

    CN103964412A

  • Carbon coated transition metal nano-composite material and preparation method and application thereof

    CN109304201A

  • Method for preparing 2, 5-furandicarboxylic acid by electro-catalyzing oxidation of 5-hydroxymethylfurfural and simultaneously electrolyzing water to prepare hydrogen

    CN112538636A

  • Preparation method and application of transition metal monatomic catalyst

    CN115722265A